High Mobility Group Box 1 Expression in Oral Inflammation and Regeneration - Yamashiro, Keisuke; Ideguchi, Hidetaka; Aoyagi, Hiroaki; Yoshihara-Hirata, Chiaki; Hirai, Anna; Suzuki-Kyoshima, Risa; Zhang, Yao; Wake, Hidenori; Nishibori, Masahiro; Yamamoto, Tadashi; Takashiba, Shogo (Frontiers in Immunology, 2020)
High mobility group box 1 (HMGB1) is a non-histone DNA-binding protein of about 30 kDa. It is released from a variety of cells into the extracellular milieu in response to inflammatory stimuli and acts on specific cell-surface receptors, such as receptors for advanced glycation end-products (RAGE), Toll-like receptor (TLR)2, TLR4, with or without forming a complex with other molecules. HMGB1 mediates various mechanisms such as inflammation, cell migration, proliferation, and differentiation. On the other hand, HMGB1 enhances chemotaxis acting through the C-X-C motif chemokine ligand (CXCL)12/C-X-C chemokine receptor (CXCR)4 axis and is involved in regeneration. In the oral cavity, high levels of HMGB1 have been detected in the gingival tissue from periodontitis and peri-implantitis patients, and it has been shown that secreted HMGB1 induces pro-inflammatory cytokine expression, such as interleukin (IL)-1β IL-6, and tumor necrosis factor (TNF)-α, which prolong inflammation. In contrast, wound healing after tooth extraction or titanium dental implant osseointegration requires an initial acute inflammation, which is regulated by secreted HMGB1. This indicates that secreted HMGB1 regulates angiogenesis and bone remodeling by osteoclast and osteoblast activation and promotes bone healing in oral tissue repair. Therefore, HMGB1 can prolong inflammation in the periodontal tissue and, conversely, can regenerate or repair damaged tissues in the oral cavity. In this review, we highlight the role of HMGB1 in the oral cavity by comparing its function and regulation with its function in other diseases. We also discuss the necessity for further studies in this field to provide more specific scientific evidence for dentistry.